Technology integration in implementing a curriculum: teachers' beliefs and willingness to change - Adnan, W.I.W.; Wahid, N.A.; Majid, N.A.; Jaafar, F.W.; Ismail, N.A. (2020)
Teachers' roles in implementing a curriculum is crucial in ensuring the planned curriculum is able to achieve its intended meaning. Accordingly, technology integration is considered essential as it perpetuates better learning outcomes for the learners. Specifically, embracing a new curriculum at classroom level requires teachers as its sole enactors to integrate any technology which accompanies an innovation. However, technology advancement does not confirm comprehensive integration. Subsequently, this conceptual paper tries to elucidate teachers' willingness to change and beliefs as predictors to successful curriculum implementation where technology integration is involved. Findings indicate that these two constructs are able to manoeuvre teachers to implement a new curriculum in a successful manner when technology integration is involved.